An Extrudable Partially Demineralized Allogeneic Bone Paste Exhibits a Similar Bone Healing Capacity as the “Gold Standard” Bone Graft - Tournier, Pierre; Guicheux, Jérôme; Paré, Arnaud; Veziers, Joëlle; Barbeito, Ana; Bardonnet, Raphaël; Corre, Pierre; Geoffroy, Valérie; Weiss, Pierre; Gaudin, Alexis (Frontiers in Bioengineering and Biotechnology, 2021)
Autologous bone grafts remain the reference grafting technique in various clinical contexts of bone grafting procedures despite their numerous peri- and post-operative limitations. The use of allogeneic bone is a viable option for overcoming these limitations, as it is reliable and it has been widely utilized in various forms for decades. However, the lack of versatility of conventional allogeneic bone grafts (e.g., blocks, powders) limits their potential for use with irregular or hard-to-reach bone defects. In this context, a ready- and easy-to-use partially demineralized allogeneic bone graft in a paste form has been developed, with the aim of facilitating such bone grafting procedures. The regenerative properties of this bone paste was assessed and compared to that of a syngeneic bone graft in a pre-clinical model of intramembranous bone healing in critical size defects in rat calvaria. The microcomputed tridimensional quantifications and the histological observations at 7 weeks after the implantation revealed that the in vivo bone regeneration of critical-size defects filled with the bone paste was similar to syngeneic bone grafts. Thus, this ready-to-use, injectable, and moldable partially demineralized allogeneic bone paste, may be of particular clinical relevance in the context of oral and maxillofacial bone reconstructions.